A new Later Upper Palaeolithic open-air site with articulated horse bone in the Colne Valley, Berkshire. (6th December 2017) - Barclay, Alistair; Bello, Silvia; Bradley, Philippa; Harding, Phil; Higbee, Lorrain; Manning, Andrew; Powell, John; Macphail, Richard; Roberts, Alison; Stewart, Mark; Barton, Nick
Abstract : The end of the last Ice Age in Britain ( c. 11500 BP) created major disruption to the biosphere. Open habitats were succeeded by more wooded landscapes, and changes occurred to the fauna following the abrupt disappearance of typical glacial herd species, such as reindeer and horse (Conneller & Higham2015 ). Understanding the impact of these changes on humans and how quickly they were able to adapt may soon become clearer, due to recent discoveries in the Colne Valley on the western edge of Greater London, north of the River Thames. An exceptionally well-preserved open-air site was discovered in 2014 as part of a wider project of archaeological investigation and excavation carried out by Wessex Archaeology (2015 ), on behalf of CEMEX UK. The site, at Kingsmead Quarry in Horton, is unusual because it has good organic preservation and, in addition to worked flint artefacts, it has yielded groups of articulated horse bone. The extreme rarity of such sites of this period in Britain makes this discovery especially significant and re-emphasises the potential importance of the Colne Valley (Lacaille1963 ; Lewis2011 ; Morgi et al .2011 ).